Design of a miniaturized multi-layer hybrid - Song, Lin Lin (2015)
The existence of Microwave (was called “radio waves” before 1946) was predicted by James Clerk Maxwell in 1864 from his equations. In 1888, Heinrich Hertz was the first to demonstrate the existence of Microwave by building a spark gap radio transmitter that produced 450 MHz microwaves, in the UHF region [1]. Since microwave has important features which other waves doesn’t contain, it has been developed and applied continuously since it’s found; now the knowledge of Microwave technology is commonly used in communication, radar and astronomy. In the microwave world, there is always a need to separate microwave power proportionally into several branches, which causes the power allocation problem. Element to achieve this function is called power allocation element device, like coupler, and based on its application, coupler could be further grouped into power dividers and directional couplers. With the development of aviation and aerospace technology and increased usage of communication devices; people are willing to accept small size, lightweight but with same or higher performance devices; hence design of miniaturized multi-layer hybrid will be beneficial to users from different areas. This paper explores the fundamental of ring coupler and concentrates on miniaturize its size using dual-layer method. It will talk about the existing design of ring coupler which consist of simulation via High Frequency Structural Simulator (HFSS) and results analysis; followed by design of half-size dual-layer ring coupler. After this, a comparison will be made between existing design and new design, also will analysis the possible reasons for differences caused. Last but not the least, hardware fabrication is mandatory for this project; hence readers will be able to see the final product and lab testing results will be introduced and compared as well.